Systemic Autoinflammatory Diseases—Clinical Rheumatic Challenges - Feist, Eugen; Feist, Eugen (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Autoinflammation, as a relatively new field in clinical rheumatology, has gained an increasing importance in recent years. The number of identified entities and affected patients has gradually increased, and some of the involved pathways have already been identified. This progress allows a deeper understanding of closely linked diseases, namely, inflammasomopathies, interferonopathies, Relo-pathies, and proteasome associated syndromes. These insights have not only improved their classification but also helped to identify new treatment targets of pro-inflammatory cytokines, including IL-1ß, IL-6, interferon-, and TNF-alpha. Nevertheless, there is still a high medical need, especially in reliable outcome measures, for confirmation of data from controlled clinical trials and, finally, also for long-term experience from registers. This issue welcomes all types of papers on the broad spectrum of clinical characteristics, prognosis, pathophysiology, and treatment of autoinflammatory diseases. The goal of this Special Issue is to further raise awareness of autoinflammatory processes and to better separate them from well-established autoimmune diseases. It is clear that we have entered a new age in this complex field, linking rheumatology even closer to immunology.
English
Keywords: Medicine; gout; febuxostat; colchicine; hepatotoxicity; prophylaxis; myositis; inflammatory idiopathic myopathy; dysphagia; aspiration; pneumonia; immunoglobulin G4-related orbital disease (IgG4-ROD); orbital lymphoma (OL); computed tomography (CT); Hounsfield unit; imaging; autoinflammation; arthritis; CAPS; FCAS; MWS; CINCA; NOMID; hearing loss; urticarial-like rash; autoinflammatory disease; anti-IL-1 treatment; rheumatoid arthritis; synovitis; neoplasms; edema; inflammation; new genetic variant; monogenic autoinflammatory syndrome; diagnostic delay; anakinra; damage index; genetic inheritance; personalized therapy; Interleukin-1; autoinflammatory diseases; FMF; coronavirus; SARS-CoV-2 antibody response; adult-onset Still s disease; autoinflammatory disorder; systemic-onset juvenile idiopathic arthritis; haemophagocytic lymphohistiocytosis; macrophage activation syndrome; IFN-; JAK inhibitor; proliferation; DNA damage repair; H2AX; PBMCs; T lymphocytes; proteasome; autoimmune; proteasome-associated autoinflammatory syndrome; therapy